Uniting Trough Sport: Legal Reflection on Sport for Development and Peace in the Indonesian Context - Julianus; Muhammad Amroe Farel Faraja; Faiz Rafif Ramadhani Yusuf (Indonesian Journal of Sports Law, 2025)
This article explores the relevance and potential of the Sport for Development and Peace (SDP) framework within the Indonesian context, particularly through the lens of national sports law. Despite the global recognition of SDP as a transformative tool for fostering inclusivity, peace, and social development, Indonesia lacks a formal legal foundation for its implementation. Drawing on a normative juridical method that incorporates statutory and conceptual approaches, the study critically analyses Law No. 11 of 2022 on Sports to evaluate its alignment with SDP values such as equity, sustainability, and social cohesion. The findings reveal that while Indonesia’s current legal framework implicitly supports several SDP principles, it falls short of offering explicit provisions or strategic policies for their integration. The paper recommends the reconstruction of existing legislation or the issuance of derivative regulations to institutionalise SDP in Indonesia. Such reforms would not only enhance the legal clarity and operational capacity of SDP programmes but also affirm Indonesia's commitment to utilising sport as a means of nation-building, youth development, and global peace advocacy.